Effects of an exoskeleton on muscle activity in tasks requiring arm elevation: Part I – Experiments in a controlled laboratory setting. - Mänttäri, Satu; Rauttola, Ari-Pekka; Halonen, Janne; Karkulehto, Jutta; Säynäjäkangas, Pihla; Oksa, Juha (Work, 2024)
BACKGROUND: Long-term work with elevated arms, or overhead work, is a risk factor for musculoskeletal complaints and disorders. Upper-limb exoskeletons are a promising tool for reducing occupational workload when working with hands above shoulder level. OBJECTIVE: The purpose of this study was to assess the effects of upper-limb exoskeleton on muscular and physical strain and perceived exertion during dynamic work at four different shoulder joint angles. Further, we evaluated if there are any negative effects associated with the use of exoskeleton. METHODS: A total of 15 student participants performed dynamic work in laboratory setting with and without an exoskeleton at four different shoulder angles: 60, 90, 120 and 150 degrees. Muscle electrical activity from 8 muscles of the upper body, perceived exertion, and heart rate were measured during the work task, and grip strength, muscle stiffness, tone, and elasticity from six muscles, m. deltoideus physiological cross-sectional area and muscle fiber pennation angle, and nerve conduction velocity were measured before and after the work task. RESULTS: Based on the results, the use of exoskeleton significantly reduced the muscle activity of the upper limb, shoulder, and back muscles. The reduction was most significant when the arm elevation was 120°, and in m. deltoideus muscle activity. RPE was also positively affected indicating reduction in workload when using exoskeleton. CONCLUSION: The results suggest that the use of upper limb exoskeleton has potential to reduce physical workload during overhead work and, consequently, reduce the risk for work-related musculoskeletal disorders.